2012
DOI: 10.1108/01409171211195170
|View full text |Cite
|
Sign up to set email alerts
|

Corporate sustainability: historical development and reporting practices

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 11 publications
1
128
0
10
Order By: Relevance
“…Data collection ended with saturation, i.e., when newly sampled texts no longer contributed to the refinement of our results. Details of the studies on corporate sustainability on which this analysis is based can be found in [16,17,[20][21][22][23][24][25][26][27][28][29][30][31][32]. The conceptual space in these articles and chapters was explored by Content Configuration Analysis (CCA) [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…Data collection ended with saturation, i.e., when newly sampled texts no longer contributed to the refinement of our results. Details of the studies on corporate sustainability on which this analysis is based can be found in [16,17,[20][21][22][23][24][25][26][27][28][29][30][31][32]. The conceptual space in these articles and chapters was explored by Content Configuration Analysis (CCA) [33,34].…”
Section: Methodsmentioning
confidence: 99%
“…These difficulties can be attributed mainly to the wide range of CSR indicators applied and the methodological approaches. Apart from that, if investors are to penalize or award firms for being socially and environmentally oriented, such activities must be available to the public in the form of self-generated reporting or third party analyses [52]. Furthermore, independent external actors must verify the presented engagement to ensure a minimum level of credibility and unselfishness.…”
Section: Corporate Social Performance and Financial Performance: The mentioning
confidence: 99%
“…2015 das empresas e problemas têm sido apontados na prática narrativa (BOUTEN et al, 2011;RICCIO, 2011;LESZCZYNSKA, 2012;CHRISTOFI;CHRISTOFI;SISAYE, 2012;TANNURI;VAN BELLEN, 2014). Índices gerais de qualidade da divulgação, que incluem elementos quantitativos para caracterizar uma boa divulgação, também têm sido disponibilizados.…”
Section: Confiabilidadeunclassified
“…Estudos acadêmicos têm buscado analisar a divulgação nos RS (DEEGAN; RANKIN, 1997;DIAS, 2006;CARVALHO, 2007;CASTRO;MACEDO, 2010;BOUTEN et al, 2011;RICCIO, 2011;LESZCZYNSKA, 2012;CHRISTOFI;CHRISTOFI;SISAYE, 2012;MORISUE;RIBEIRO;PENTEADO, 2013;TANNURI;VAN BELLEN, 2014), mas não foram encontrados trabalhos que tenham analisado as características de acurácia das informações reportadas, de acordo com os critérios propostos neste trabalho. O estudo busca contribuir na discussão acadêmica sobre a accountability da sustentabilidade e na análise das informações contábeis necessárias para um relato de qualidade nas divulgações socioambientais.…”
Section: Introductionunclassified